2010
DOI: 10.1007/s11934-010-0118-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Botulinum Toxcin Use for Chronic Pelvic Pain Syndrome

Abstract: The inability of urologists to consistently and effectively treat men with chronic pelvic pain syndrome (CPPS), also known as chronic abacterial prostatitis, is a source of great frustration. Botulinum toxin (BTX), a potent neurotoxin, can act on most of the peripheral nerves of the pelvis through a variety of mechanisms. BTX injection therapy for CPPS treatment has shown modest improvements. BTX is ideal for integration into a multimodal treatment plan, which may help achieve pain relief in men with chronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These studies used different routes of injections (transurethral, transrectal and transperineal), different doses of BTX-A (30-200 U) and different outcome variables (uroflowmetry, visual pain analogue score, pelvic floor tenderness, Global Response Assessment and total CPSI) [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…These studies used different routes of injections (transurethral, transrectal and transperineal), different doses of BTX-A (30-200 U) and different outcome variables (uroflowmetry, visual pain analogue score, pelvic floor tenderness, Global Response Assessment and total CPSI) [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there are few clinical trials evaluating the role of BTX-A in patients with CP/CPPS, and only one was designed as a controlled study. These studies used different routes of injections (transurethral, transrectal and transperineal), different doses of BTX-A (30–200 U) and different outcome variables (uroflowmetry, visual pain analogue score, pelvic floor tenderness, Global Response Assessment and total CPSI) [24–29] .…”
Section: Discussionmentioning
confidence: 99%
“…There have been no large, randomized trials, however, that have demonstrated statistically significant improvement or durability. Because of the favorable results in women with IC/PBS and the potentially numerous targets for botulinum in UCPP in men, it may play an important role in a "polytherapeutic approach" [38].…”
Section: Management Of Lower Urinary Tract Symptoms Associated With Umentioning
confidence: 99%